The Concept of Educational Management at Ma'had Aly Al Mukmin - Nurdin Urbayani; Rakhmad Agung Hidayatullah; Akbar Rizki; Ahmad Fauzan; Amir Reza Kusuma (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Educational management is a fundamental order in the implementation of education that is applied in the development of education. So in this discussion, Islamic educational management is interpreted as the art and science of managing Islamic educational resources to achieve Islamic educational goals effectively and efficiently in planning, implementation and results. Therefore, basic knowledge is needed in order to form a perfect and in-depth understanding of the science being studied, namely, an understanding of the concept of Islamic educational management that takes the perspective of the Qur'an, As-Sunnah and applicable laws as the basis for implementing Islamic educational management. by using this research analysis method, it produces the learning method applied in Ma'had Aly Al Mukmin currently there are three methods or learning systems. Namely intracurricular, co-curricular, and extracurricular. The intracurricular learning method is the core learning method or the main learning that we can later convey to students.